2019
DOI: 10.30659/odj.6.0.56-61
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Gingival Recession Coverage Treated With Vista Technique Using Acellular Dermal Matrix (Adm) Combined With Platelet Rich Fibrin (Prf): A Case Report

Abstract: Background: Gingival recession is an exposure of the root surface due to migration of the marginal periodontal tissues apical to the cemento enamel junction. There are so many root coverage procedures, among these techniques, VISTA technique combined with ADM and PRF offers minimally invasive approach.Case Management: A-40-year-old male visited Periodontics Clinic of DentalHospital Airlangga University with the chief complaint of poor aesthetic resulting from exposed root surfaces in upper right front region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This result was compatible with our study suggesting the use of VISTA technique with ADM. Gupta et al 2015, 33 found that using VISTA technique along with plateletrich fibrin provided optimal esthetic results and perfect soft tissue biotype. Also Pratiwi & Setiawatie 2019 34 , in a case report used minimal invasive VISTA technique with ADM and platelet rich fibrin in treatment of multiple gingival recessions. They found that VISTA technique was effective in maintaining vascularity and papillary integrity.…”
Section: Disscussionmentioning
confidence: 99%
“…This result was compatible with our study suggesting the use of VISTA technique with ADM. Gupta et al 2015, 33 found that using VISTA technique along with plateletrich fibrin provided optimal esthetic results and perfect soft tissue biotype. Also Pratiwi & Setiawatie 2019 34 , in a case report used minimal invasive VISTA technique with ADM and platelet rich fibrin in treatment of multiple gingival recessions. They found that VISTA technique was effective in maintaining vascularity and papillary integrity.…”
Section: Disscussionmentioning
confidence: 99%